(untitled) (Conferencea, 2022)
The paper analyzes the methods and methods for calculating and testing the strength of wheels used on rolling stock of railways. The purpose of this study is to study the basic requirements of the technical conditions of production, standards for the calculation and testing of railway wheels, compare domestic and foreign calculation standards, and identify their advantages and disadvantages. The paper describes the method of strain measurement, the measurement of residual stresses by the ultrasonic method, and the X-ray method of measurement. It has been determined that the results of an experimental assessment of the stress-strain state of railway wheels, first of all, should be based on the experience of conducting the following type tests: determination of residual stresses; measurement of stresses on the disk surface during fatigue tests; determination of the stress-strain state during long-term braking by the shoes.